Mode identification in impact-induced high-frequency vehicular driveline vibrations using an elasto-multi-body dynamics approach - Stephanos Theodossiades; M. Gnanakumarr; Homer Rahnejat; M.T. Menday (2004)
The paper describes a noise, vibration and harshness (NVH) phenomenon caused by impact of meshing gear teeth pairs, resulting in structural wave propagation and elastoacoustic coupling in the driveline system, referred to in industry as clonk. The numerical investigation combines multi-body dynamics analysis with flexible body oscillation behaviour predicted by finite element analysis (FEA) techniques. Particular attention is paid to local non-linearities such as the varying stiffness of meshing gear teeth and their normal backlash. The spectrum of vibration of lightly damped hollow driveshaft tubes shows good conformity with experimental results.